Staphylococcus aureus Manipulates Innate Immunity through Own and Host-Expressed Proteases - Pietrocola, Giampiero; Nobile, Giulia; Rindi, Simonetta; Speziale, Pietro (Frontiers in Cellular and Infection Microbiology, 2017)
Neutrophils, complement system and skin collectively represent the main elements of the innate immune system, the first line of defence of the host against many common microorganisms. Bacterial pathogens have evolved strategies to counteract all these defence activities. Specifically, Staphylococcus aureus, a major human pathogen, secretes a variety of immune evasion molecules including proteases, which cleave components of the innate immune system or disrupt the integrity of extracellular matrix and intercellular connections of tissues. Additionally, S. aureus secretes proteins that can activate host zymogens which, in turn, target specific defence components. Secreted proteins can also inhibit the anti-bacterial function of neutrophils or complement system proteases, potentiating S. aureus chances of survival. Here, we review the current understanding of these proteases and modulators of host proteases in the functioning of innate immunity and describe the importance of these mechanisms in the pathology of staphylococcal diseases.